2015
DOI: 10.1002/bio.2990
|View full text |Cite
|
Sign up to set email alerts
|

A selective determination of copper ions in water samples based on the fluorescence quenching of thiol‐capped CdTe quantum dots

Abstract: CdTe quantum dots (QDs) capped with different stabilizers, i.e. thioglycolic acid (TGA), 3-mercaptopropionic acid (MPA) and glutathione (GSH) were investigated as fluorescent probes for the determination of Cu(2+). The stabilizer was shown to play an important role in both the sensitivity and selectivity for the determination of Cu(2+). TGA-capped CdTe QDs showed the highest sensitivity, followed by the MPA and GSH-capped CdTe QDs, respectively. The TGA- and MPA-capped CdTe QDs were not selective for Cu(2+) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…No significant interference could be observed from the investigated metal ions. Interestingly, Ag + was not observed as an interferent as reported elsewhere, using TGA and MPA as ligands . Therefore, the present sensor acts as a potential candidate for the sensing of Cu 2+ without the need for separation of interferents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant interference could be observed from the investigated metal ions. Interestingly, Ag + was not observed as an interferent as reported elsewhere, using TGA and MPA as ligands . Therefore, the present sensor acts as a potential candidate for the sensing of Cu 2+ without the need for separation of interferents.…”
Section: Resultsmentioning
confidence: 99%
“…A comprehensive study on the performance of CdTe@E2MP sensor among other CdTe QDs based sensors is performed and the results are tabulated in Table 1. The CdTe@E2MP sensor is comparable with other CdTe QDs based sensors capped with different capping ligands like TGA, MPA, GSH etc.. [7,27,[45][46][47][48][49][50][51]…”
Section: Fluorescence Quenching Of Cdte@e2mp Qds By Cu 2 +mentioning
confidence: 89%
“…Although these techniques can be utilized to detect Cu 2+ , they are complicated, utilizing expensive instruments and requiring a time‐consuming sample pre‐treatment. To overcome these problems, fluorescence spectroscopy has attracted interest as the high‐performance alternative method for the fast determination of Cu 2+ because of several advantages, such as high sensitivity, specificity and ease of operation. Several fluoroionophores have been developed for Cu 2+ by utilising the excellent molecular recognition ability of cyclam (Scheme ) in ‘fluorophore‐spacer‐receptor’ mode .…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these problems, fluorescence spectroscopy has attracted interest as the high‐performance alternative method for the fast determination of Cu 2+ because of several advantages, such as high sensitivity, specificity and ease of operation. Several fluoroionophores have been developed for Cu 2+ by utilising the excellent molecular recognition ability of cyclam (Scheme ) in ‘fluorophore‐spacer‐receptor’ mode . However, these fluorescent methods are also limited by complex organic synthesis, harmful organic co‐solvent system, autofluorescence background, excitation power fluctuation, photobleaching, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that water-soluble QDs could be used as selective inorganic ion probes to determining CN À , H + , Ag + , Hg 2+ , Cu 2+ , Fe 2+ , Ni 2+ , Pb 2+ , Mn 2+ , Zn 2+ , and Co 2+ (22)(23)(24)(25)(26)(27). Interestingly, cationic dyes and surfactants can quench QDs extensively (28,29).…”
Section: Introductionmentioning
confidence: 99%